2007
DOI: 10.1016/j.jenvman.2006.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a stratified sand filter in removal of chemical oxygen demand, total suspended solids and ammonia nitrogen from high-strength wastewaters

Abstract: A stratified sand filter column, operated in recirculation mode and treating synthetic effluent resembling high-strength dairy wastewaters was studied over a 342-d duration. The aim of this paper was to examine the organic, total suspended solids (TSS) and nutrient removal rates of the sand filter, operated in recirculation mode, under incrementally increasing hydraulic and organic loading rates and to propose a field filter-sizing criterion. Best performance was obtained at a system hydraulic loading rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 17 publications
6
14
0
4
Order By: Relevance
“…A correlation coefficient r of 0.97 was observed between the CoD removal percentages and the abundances of aerobic bacteria in the three-step series CRi system, indicating that the correlation was very obvious. This also indicated that microbes were playing a key role in the removal of organic matter, which was in agreement with some previous studies [10][11][12][13][14][15].…”
Section: Distribution Of Aerobic Ammonifying Bacteriasupporting
confidence: 93%
“…A correlation coefficient r of 0.97 was observed between the CoD removal percentages and the abundances of aerobic bacteria in the three-step series CRi system, indicating that the correlation was very obvious. This also indicated that microbes were playing a key role in the removal of organic matter, which was in agreement with some previous studies [10][11][12][13][14][15].…”
Section: Distribution Of Aerobic Ammonifying Bacteriasupporting
confidence: 93%
“…4 shows an important reduction of the TSS as of the starting of filter operation (90%), this reduction remains always important until the clogging of the filter, and it varies between 75 and 90%. According to Healy et al (2007), significantly higher TSS removal (100%) was observed during the treatment of synthetic effluent resembling highstrength dairy wastewaters.…”
Section: Reduction Of Total Suspended Solids (Tss)mentioning
confidence: 99%
“…Healy et al [12] found similar results when a laboratory sand filter was loaded with synthetic wastewater at TSS loading rates ranging from 5.2 to 12 g m -2 d -1 . In filters loaded with medium-to high-strength wastewaters, a biofilm layer forms as a schmutzedecke on the filter surface.…”
Section: Organic Carbon and Tss Removalmentioning
confidence: 66%
“…Intermittently loaded sand filters have also been successfully used to treat high-strength wastewater. [11,12] A novel horizontal flow biofilm reactor (HFBR) for treating wastewater, comprising a stack of about 40 horizontal polyvinyl chloride sheets, positioned over one another, has been developed by researchers at the National University of Ireland, Galway. [13] In this system, wastewater is intermittently pumped onto the top of the stack.…”
Section: Domestic Wastewater Treatment By Septic Tanks and Percolatiomentioning
confidence: 99%